THE EFFECTS OF VARYING INCLUSION LEVELS OF Saccharomyces cerevisiae AND INCUBATION PERIODS ON AQUA-FEED BUOYANCY - ORIRE, A. M; FACHE, P.O.; SADIKU , S.O.E (Nigerian Journal of Fisheries, 2015)
The production of on-farm non sinking pellets remains a challenge to fish farmers which necessitated for over reliance on imported extruded feeds. Most sinking feeds pollute water and are unavailable to fish for growth. In this research, the effect of varying inclusion levels of Saccharomyces cerevisae (floating catalyst) and varying incubation periods on feed buoyancy. Four feeds were formulated to contain the floating catalyst at 5%, 7.5%, 10% and 12.5% inclusion levels and each was incubated for 30, 45 and 60 minutes at 38 ºC respectively. The buoyancy test was conducted on the feeds and the results indicated significant effects of the treatments on feed buoyancy. The feed with 7.5 % floating catalyst and 30 minutes incubation had 95% floating rate for 60 minutes on water while, that which had 5% floating catalyst performed best at 60 minutes incubation with 85% floating rate for 60 minutes. The result indicated that, appropriate inclusion of bakers' yeast and incubation period with right feed constituents on feed constituents will produce desirable floating feed for aquatic organism